Cryptocurrency Bitcoin Dalam Pengupahan Karyawan Indonesia - Rizki Firmansyah, Mohammad (International Forum of Researchers and Lecturers, 2023)
. In the development of this massive information system, all countries in the world are competing to modernize to benefit their countries, not only in the form of technology, but also into the economic field. In the economy is also known as a payment system that can be carried out by a person or a company in making transactions and so on. Transactions in the realm of companies can also be associated with the payment of salaries to employees or laborers. In paying wages to employees, of course, you can use any currency depending on the agreement by both parties, namely the company and the employees themselves. For example, payments using Bitcoin as a means of paying wages or salaries to laborers. This research uses an analytical descriptive method in the form of a literature study by discussing how the legality of Bitcoin in Indonesia as a means of payment and how to guarantee employee rights paid through Bitcoin..